Clinical Outcomes of Neoadjuvant Chemotherapy in Colorectal Cancer Patients With Synchronous Resectable Liver Metastasis: A Propensity Score Matching Analysis - Sung Hae Park; Jung Kyong Shin; Woo Yong Lee; Seong Hyeon Yun; Yong Beom Cho; Jung Wook Huh; Yoon Ah Park; Jin Seok Heo; Gyu Seong Choi; Seung Tae Kim; Young Suk Park; Hee Cheol Kim (Annals of Coloproctology, 2021)
Purpose The survival benefit of neoadjuvant chemotherapy (NAC) prior to surgical resection in colorectal cancer with liver metastases (CRCLM) patients remains controversial. The aim of this study was to compare overall outcome of CRCLM patients who underwent NAC followed by surgical resection versus surgical treatment first. Methods We retrospectively analyzed 429 patients with stage IV colorectal cancer with synchronous liver metastases who underwent simultaneous liver resection between January 2008 and December 2016. Using propensity score matching, overall outcome between 60 patients who underwent NAC before surgical treatment and 60 patients who underwent surgical treatment first was compared. Results Before propensity score matching, metastatic cancer tended to involve a larger number of liver segments and the primary tumor size was bigger in the NAC group than in the primary resection group, so that a larger percentage of patients in the NAC group underwent major hepatectomy (P < 0.001). After propensity score matching, demographic features and pathologic outcomes showed no significant differences between the 2 groups. In addition, there was no significant difference in short-term recovery outcomes such as postoperative morbidity (P = 0.603) and oncologic outcome, including 3-year overall survival rate (P = 0.285) and disease-free survival rate (P = 0.730), between the 2 groups. Conclusion NAC prior to surgical treatment in CRCLM is considered a safe treatment that does not increase postoperative morbidity, and its impact on oncologic outcome was not inferior.